Two-Wheel Patrol Optimization of Satuan Samapta in Order to Prevent Vehicle Theft in Temanggung Police Jurisdiction - yohananda fajri - (Tanggon Kosala, 2023)
The goal of this study is to answer the writer's problem, why Satuan Samapta's Temanggung Police two-wheel patrol in order to prevent vehicle theft wasn't optimal. In this research, the writer will describe the implementation and patrol method of Satuan Samapta’s two-wheel patrol in order to prevent vehicle theft in Temanggung police jurisdiction. This study uses a qualitative approach. qualitative methode used as a procedure to generate descriptive data such as words written or verbal from people and behavioral observed. The focus of this research is the preventive implementation optimization by Satuan Samapta’s Unit Turjawali through twowheel patroli in order to prevent vehicle theft in Temanggung police jurisdiction. Primary data was gathered by doing interviews with 6 people and secondary data was gathered by scripts. Data validation uses source, method, and theory triangulation. The results of this study indicate that the management of four-wheel patrol analyzed with management theory and prevention crime theory wasn’t optimal. The lack of implementation in two-wheel patrol and from un-done patrol method causes Satuan Samapta’s two-wheel patrol wasn’t optimal.